Investigación de diseños de mezcla para producir Ultra High Performance Fiber Reinforced Concrete (UHPFRC) usando ANOVA - Rojas de Yepez, Rosangel (2019)
An experimental study is presented to produce Ultra High Performance Fiber Reinforced Concrete (UHPFRC) including industrial waste in the mix, and determine the average compressive strength. The study includes factor arrangements to perform analysis of variance using ANOVA. The controllable factors were: (i) age of the sample; (ii) granulometry of the slag; (iii) mix designs; (iv) percentages of fibers and (iv) ther-mal treatment in curing. The highest resistance values obtained were 138.12, 132.17 and 155.29 MPa, with partial substitutions of cement by industrial waste of 35, 25 and 26% respectively. The mixing designs were manufactured using a simple procedure, using materials such as cement, silica fume, blast furnace slag, quartz powder and fine sand produced in Brazil. Also, the mixture includes the superplasticizer diluted in water and the fibers, which are incorporated when the mixture becomes a dense plastic mass. The results showed that all the controllable factors have significant influence on the response variable, and that the pro-bability that the variations in resistance are attributed to the experimental error is less than 1 ‰.